Journalism teaching in the knowledge society - La Rosa Pinedo, Amaro (2008)
This paper pretends ro show a general vision about rhe impact produced on society in general, and journalism in panicular, due to che development of the New Information and Communication Technologies (NICT). Scarting on the analysis of the lnternet's role in this contemporary world, the labor market is analyzed then, and finally it is given an appreciation on the requirements of che Knowledge  Society for universities, teachers and students.